Exploring Generational Differences and Contents of Psychological Contract - Gamage, Prasadini N; Thisera, T. (Gyan Management Journal)
In the contemporary business environment organizations have to carry out their business activities in more competitive way. One of the biggest challenges faced by the modern organizations is to retain satisfied and productive workforce over the other competitors in the market. In order to accomplish that it is essential to understand and cater to fulfill the contents of Psychological Contract perceived by employees when they join the organization. This study attempts to identify the relationship between different generations and contents of the Psychological Contract.The sample of the study consists of 89 employees in executive level working in five insurance companies in Sri Lanka. The independent variable of the study is generations consisted of Baby Boomers, Generation X and Y. The dependent variable is contents of Psychological Contract. Here researchers consider only job security and challenging jobs under the contents of Psychological Contract. To gather data a structured questionnaire was distributed among the respondents and data were analyzed by using independent sample t-test technique. The statistical results of the study showed that perceived expectation of job security among Baby Boomers is higher than employees belonging to Generation X and Y, but the perceived expectation of challenging jobs is higher among employees belonging to Generation X and Y than Baby Boomers.